‘Targeting the feast of a sleeping beast’: Nutrient and mineral dependencies of encysted Acanthamoeba castellanii - Baig, A. M.; Khan, N. A.; Katyara, P.; Lalani, S.*; Baig, R.; Nadeem, M.; Akbar, N.; Nazim, F.; Khaleeq, A. (Wiley, 2020)
Acanthamoeba spp. cause a corneal infection, Acanthamoeba keratitis (AK), and a cerebral infection, granulomatous amoebic encephalitis (GAE). Though aggressive chemotherapy has been able to kill the active trophozoite form of Acanthamoeba, the encysted form of this parasite has remained problematic to resist physiological concentrations of drugs. The emergence of encysted amoeba into active trophozoite form poses a challenge to eradicate this parasite. Acanthamoeba trophozoites have active metabolic machinery that furnishes energy in the form of ATPs by subjecting carbohydrates and lipids to undergo pathways including glycolysis and beta‐oxidation of free fatty acids, respectively. However, very little is known about the metabolic preferences and dependencies of an encysted trophozoite on minerals or potential nutrients that it consumes to live in an encysted state. Here, we investigate the metabolic and nutrient preferences of the encysted trophozoite of Acanthamoeba castellanii and the possibility to target them by drugs that act on calcium ion dependencies of the encysted amoeba. The experimental assays, immunostaining coupled with bioinformatics tools show that the encysted Acanthamoeba uses diverse nutrient pathways to obtain energy in the quiescent encysted state. These findings highlight potential pathways that can be targeted in eradicating amoebae cysts successfully.